Prevalence and Incidence of Chondral and Meniscal Lesions in Patients Undergoing Primary and Subsequent Revision Anterior Cruciate Ligament Reconstruction: An Analysis of 213 Patients From the SANTI Group. Issue 7 (June 2022) - Pioger, Charles; Claes, Steven; Haidar, Ibrahim; Fradin, Thomas; Ngbilo, Cedric; Rayes, Johnny; Hopper, Graeme Philip; Vieira, Thais Dutra; Sonnery-Cottet, Bertrand
Background: Previous studies have shown a higher prevalence of meniscal and chondral lesions at the time of revision anterior cruciate ligament reconstruction (R-ACLR) compared with primary ACLR procedures. However, studies that follow the development of meniscal and chondral status through primary and subsequent R-ACLR are scarce. Purpose: To compare the prevalence of meniscal and chondral injuries in patients undergoing primary ACLR and subsequent R-ACLR. Study Design: Case series; Level of evidence, 4. Methods: Patients who underwent ACLR and subsequently needed R-ACLR between January 2009 and February 2018 in a single center were included. A retrospective analysis of prospectively collected data was conducted. Results: A total of 213 patients were included, with a mean follow-up of 59.7 months. The mean age was 22 years at primary ACLR and 26.1 years at the time of revision. The proportion of meniscal tears was higher at the time of R-ACLR compared with the time of primary reconstruction (70.0% vs 44.6%, respectively; P < .001). Similarly, the prevalence of chondral lesions was significantly higher at the time of revision versus the primary reconstruction (15.5% vs 7.0%, respectively; P = .003). Conclusion: R-ACLR is associated with a higher rate of concomitant meniscal and chondral lesions than primary ACLR.